Student’s perception to learning of innovative skills through multidimensional visualization system: Reliability and validity tests of some measurements - Muraina, Ishola Dada; Ibrahim, Huda (2016)
Learning has been described as the process of obtaining new knowledge, skills and habits, and can be subjective to the individual preparedness to learn, especially in the context of gaining the innovative skills.Knowing the perception of student’s towards learning of innovative skills would assist the management and teachers on the appropriate approach for teaching. However, there has been less or no research that focuses on bringing the perception of students towards the learning of innovative skills into reality prior to the commencement of teaching. Therefore, a Multi Dimensional Visualization system is proposed in this research to reveal the level of perception of students towards learning of innovative skills in university set up by adapted Expectation Confirmation Model.An experiment was conducted by engaging 200 undergraduate students within the university campus so as to measure their level of perception towards learning of innovative skills using the proposed system.A measurement model analytical technique from the perspective of Partial Least Square of Structural Equation Model was used to confirm the reliability and validity of the proposed system, while the result shows high accuracy.This research gives useful hints for the university’s management by obtaining the perception of student prior to learning of innovative skills.